Remembrance of Allah: A Reflection on Selected Qur’anic Verses - Prof Dr Israr Ahmad Khan (jihat-ul-islam, 2023)
The Qur’an describes in the most crystal-clear manner the two quintessential elements in the constitution of human being, extract of clay[i] and essence of the Divine Spirit[ii]. The perfect fusion of these two elements resulted in the appearance of an intellectual, hence moral being i.e., human being. The nature of human beings calls for equilibrium in all human thoughts and actions. Equilibrium in humans can be maintained only by doing justice to both earthly propensities and heavenly attributes inherent in human beings. Justice is almost impossible if both dimensions of humans (earthly and heavenly) are treated in isolation from each other. Laying emphasis on the heavenly nature of humans and ignoring earthly traits amount to tremendous damage to the moral existence of humans. Many a quarter of all religious denominations subscribe to the erroneously conceived belief in what is termed as “spirituality”. Strangely enough, those who claim spiritual dimension in human life and activities have miserably failed to define “spirituality”. Muslim scholars, without any exception, have fallen prey to the onslaught of Greek and Vedant philosophies which attach too much emphasis on “spirituality” at the cost of material aspect of humanity. They do not have any sustainable evidence to support the idea concerning “spirituality”. Their only proof to confirm the notion of “spirituality” is the Qur’anic statement that human is created out of, besides extract of clay, Divine Spirit. Why do they ignore the fact that human existence is the outcome of the perfect blend of both matter and spirit. After the amalgamation of the two there is no way to identify material segments and spiritual aspects separately. What can certainly be identified in human life is the intellectual/moral facet. It is this reason that the Qur’an eulogizes the Last Prophet (s.a.w.) as the figure of moral excellence: “O Prophet, you are indeed on the unparalleled standard of moral excellence”[iii]. The original Qur’anic word to introduce the Last Prophet (s.a.w.) is “khuluq ‘azeem” (moral excellence). Why did not the Qur’an describe the Last Prophet (s.a.w.) as a “person of spiritual excellence”? It is because the human being is certainly a moral being, not a spiritual being. To divide human life into two mutually conflicting parts, material and spiritual, is entirely uncalled for. Human beings carry only one dimension i.e., moral dimension. Those who insist on bifurcating humans into material and spiritual facets in isolation from each other tend to create imbalance in human life and activities. The only sure way to maintain balance in human life and activities is remembrance of Allah, the Creator, the Sustainer, the Provider, the Caretaker, the controller of the universe, the Most Beneficent, the Most Magnificent, the Authority on the Day of Judgment. It is noteworthy that remembering Allah is not a spiritual act but an intellectual exercise hence a moral act. [i] Al-Mu'minun: 12 [ii] Al-Hijr: 29 ; Al-Sajdah, 9 [iii] Al-Qalam,: 4